Impact of Oseltamivir and Diabetes Development - Bor-Show Tzang; Chih-Chen Tzang; Pei-Hua Chuang; I-Ying Kuo; Yu-Chun Pan; Pei-Hsun Wu; Tsai-Ching Hsu (Pharmaceuticals, 2025)
Background/Objectives: Influenza is a major global health challenge, causing thousands of deaths annually. Antiviral drugs, particularly oseltamivir, a neuraminidase inhibitor, have become essential therapeutic options due to their oral bioavailability and efficacy. Previous studies suggest a potential association between oseltamivir use and the onset of diabetes mellitus. However, further investigation is needed to establish a definitive link. Methods: This retrospective cohort study utilized data from the Taiwan National Health Insurance Research Database (NHIRD), including 1,631,968 patients (815,984 oseltamivir users) between 1 January 2009 and 28 December 2018. All statistical analyses were performed using SAS 9.4M8 software (SAS Institute Inc., Cary, NC, USA). Results: Cox proportional hazards regression and multivariate analyses revealed a statistically significant association between oseltamivir use and overall diabetes risk (HR = 1.027, p = 0.0186). While no significant association was observed for Type 1 diabetes (HR = 1.021; p = 0.06795), oseltamivir users showed a higher incidence of Type 2 diabetes (HR = 1.024; p < 0.05). Oseltamivir was also linked to increased risks of comorbidities, including dyslipidemia (HR = 1.295, p < 0.0001), chronic liver disease (HR = 1.446, p < 0.0001), hypertension (HR = 1.586, p < 0.0001), and obesity (HR = 2.949, p < 0.0001). Conclusions: Oseltamivir is associated with an increased risk of Type 2 diabetes but not Type 1, and related comorbidities.